Ischemic Optic Neuropathy Following Spine Surgery: Case Control Analysis and Systematic Review of the Literature. Issue 15 (1st August 2019) - Goyal, Anshit; Elminawy, Mohamed; Alvi, Mohammed Ali; Long, Timothy R.; Chen, John J.; Bradley, Elizabeth; Freedman, Brett A.; Bydon, Mohamad
Abstract : Study Design: Case–control analysis and systematic literature review. Objective: To illustrate the prognosis and perioperative risk factors associated with this condition. Summary of Background Data: Ischemic optic neuropathy (ION) is the most common pathological diagnosis underlying postoperative vision loss. It comes in two primary forms—anterior (AION)—affecting the optic disc or posterior (PION) affecting the optic nerve proximal to the disc. Spine surgery remains one of the largest sources of acute perioperative visual loss. Methods: We performed a 1:4 case–control analysis (by age and year of surgery) for patients with ION and those who didn't develop ION following spine surgery at our institution. A systematic literature search of Medline, Embase, Scopus from inception to September 2017 as also performed. Results: We identified 12 cases from our institution. Comparison to 48 matched controls revealed fusion, higher number of operative levels, blood loss, and change in hemoglobin, hematocrit to be significantly associated with ION. Majority were diagnosed with PION (83%, 10/12) and had bilateral presentation (75%, 9/12). Only 30% patients (3/10) demonstrated improvement in visual acuity while the rest remained either unchanged (40%, 4/10) or worsened (20%, 2/10) at last follow-up. Literature review identified 182 cases from 42 studies. Posterior ischemic optic neuropathy (PION) was found in 58.7% (114/194) of cases, anterior ischemic optic neuropathy (AION) in 17% (33/19) and unspecified ION in 24% (47/194). PION was associated with higher odds of severe visual deficit at immediate presentation (odds ratio [OR]: 6.45, confidence interval [CI]: 1.04–54.3, P  = 0.04) and last follow-up. Conclusion: PION is the most common cause of vision loss following spine surgery and causes more severe visual deficits compared with AION. Prone spine surgery especially multi-level fusions with longer operative time, higher blood loss, and intraoperative hypotension are most associated with the development of this devastating complication. Level of Evidence: 3 Abstract : Supplemental Digital Content is available in the textSpine surgery remains one of the most common causes of perioperative vision loss due to ischemic optic neuropathy. We present a case series and systematic review of the literature to illustrate risk factors and prognosis and highlight the need for better reporting of this rare but devastating complication of spine surgery.